Reinforcement and MAO-A inhibition in heated tobacco products: flavor and brand variations - Xiangyu Li; Xiangyu Li; Zheng Ding; Zheng Ding; Xingyi Jiang; Xingyi Jiang; Hongjuan Wang; Hongjuan Wang; Yanbo Luo; Yanbo Luo; Huan Chen; Huan Chen; et al. (Frontiers in Psychiatry)
ObjectiveThis study investigates the reinforcing effects and monoamine oxidase-A (MAO-A) inhibitory properties of heated tobacco products (HTPs), comparing them to nicotine alone. It also examines brand-specific differences in MAO-A inhibition to provide a deeper understanding of the role of non-nicotine constituents in HTP use.MethodsA rat self-administration model was used to evaluate the reinforcement patterns of HTP-T (tobacco flavor), HTP-M (menthol flavor), and nicotine under fixed-ratio schedules. In vitro assays were performed to measure the MAO-A inhibitory effects of nicotine, HTP-T, and HTP-M. Additionally, chemical composition analyses of HTP-T and HTP-M aerosols were conducted and compared to identify potential MAO inhibitors. Finally, in vitro assessments of MAO-A inhibition were performed across various HTP brands to determine whether significant differences in MAO-A inhibition exist among different HTP products.ResultsHTP-T showed self-administration patterns comparable to nicotine, while HTP-M demonstrated significantly higher reinforcement. In vitro analyses revealed that both HTP-T and HTP-M exhibited MAO-A inhibition at high nicotine-equivalent concentrations (>10−2–10−1 mM), with HTP-M showing stronger inhibition. In contrast, Nicotine alone showed no MAO-A inhibition. Brand-specific differences in MAO-A inhibitory effects were also observed, potentially driven by variations in aerosol composition.ConclusionsHTP-M's enhanced reinforcement could be attributed to its higher MAO-A inhibition and menthol's synergistic effects on nicotine. Brand-specific variations in MAO inhibition highlight the impact of non-nicotine constituents on HTP use. While this study provides valuable insights into HTPs, its reliance on animal models and in vitro assays highlights the necessity for human studies conducted under real-world conditions.